Making Sense of Madness: Revisiting R.D. Laing. (31st March 2018) - Ferguson, Iain
Abstract : The 1960s saw a challenge to the dominant ideas not only in areas such as women's oppression and the position of black people, but also in relation to mental health. A central figure, perhaps the central figure, in these debates around mental health and 'mental illness' was the Scottish psychiatrist and psychoanalyst R.D. Laing. This article aims to provide an outline of Laing's key ideas and activities, and to assess the extent to which these ideas are still of value for those seeking to develop less medicalised responses to mental distress in the context of the current crisis in mental health.